P1_1_Delta Doping Limitations in Example Semiconductor GaAs_V2 - Feeley, Mathew; Benson, Lucy; Nguyen, Minh Hai (Physics Special Topics, 2009)
Abstract. In this paper, a limit for the application of the use of the Dirac delta function as an approximation for the doping profile of very thin semiconductor dopant layers is deduced.